PENGARUH CITA RASA, KUALITAS PRODUK DAN PRESEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PABRIK TAHU BAPAK WITO DI KELURAHAN LEDOK KULON BOJONEGORO - Elliza Firnanda; Estik Hari Prastiwi (CV SWA Anugrah, 2024)
Tofu is a type of soy-based protein food that is popular among Indonesian people. In Bojonegoro, precisely in Ledok Kulon Village, which is located 500 meters from the Bojonegoro government center, you can also find many tofu producers. Ledok Kulon Village has been the first and largest producer of Bojonegoro tofu since 1918 and continues to this day. Currently there are 161 producers who are still actively producing tofu in the region. Increasingly fierce commercial competition, especially in the food sector, means that industry must act more quickly to attract consumers. Therefore, Mr Wito's Tofu Factory must pay special attention to consumers and the factors that influence purchasing decisions.The aim of this research is to find out how influential taste, product quality and price perception are on consumer purchasing decisions at Mr Wito's tofu factory in Ledok Kulon Bojonegoro Village. This research uses a type of quantitative descriptive research that uses primary data obtained through interviews and research questionnaires. The population and sample used were 100 respondents. To test partially use the t test and to test simultaneously use the F test. Meanwhile, the classical assumption tests used include the normality test, multicollinearity test, heteroscedasticity test. And data analysis uses multiple linear regression with the help of SPSS (Statistical Package for Social Science) version 25 software. Based on the results of data analysis, it shows that simultaneously taste, product quality and price perception influence purchasing decisions at Mr Wito's Tofu Factory in Ledok Kulon Bojonegoro Village. And partially taste, product quality and price perception have a significant influence on purchasing decisions at Mr Wito's Tofu Factory in Ledok Kulon Bojonegoro Village. The results of multiple linear regression based on the formula Y = a + + + + e show that the variables taste (X1), product quality (X2), and price perception (X3) influence purchasing decisions (Y).